The Mainstreaming of Egalitarian Pedagogy in Sociology Learning Process - ., Abdurrohman; Made Pageh, I; Wayan Mudana, I; Ketut Margi, I; Kerti Nitiasih, Putu (KnE Social Sciences, 2024)
The purpose of this study was to determine the practice of teaching sociology using an egalitarian pedagogy approach in the Practice of Field Experience (PPL) II of Teacher Professional Education Program (PPG) Pre-service at SMAN 1 Masbagik, East Lombok. The method of this research was qualitative research with a phenomenological approach. The subjects of this study were students of the PPL II of PPG Pre-service at SMAN 1 Masbagik, East Lombok. Data collection techniques were observation, interviews, and documentation, while the data analysis technique used was interpretative phenomenological analysis. In the practice of learning sociology at PPL II PPG Pre-service, students as professional teacher candidates applied innovative learning models such as discovery and inquiry learning, Project Based Learning (PjBL), Problem Based Learning (PBL), and Cooperative Learning. These learning models emphasize student-centered learning where students are encouraged to be active, independent, critical, creative, interactive, and collaborative. At this point, the practice of learning sociology prioritizes group discussions, problem solving through case studies and assignments (field studies). Besides applying innovative learning models, students from the Field Experience Practice (PPL) II PPG Pre-service also used an egalitarian pedagogical approach, namely sociology learning which was designed to be more fun and meaningful so as to create learning that is more humane, dialogical, and participatory. Learning here is interpreted as learning together so as to create an egalitarian relationship between the teacher and students in the classroom where the teacher acts more as a facilitator, motivator, and inspirer. Keywords: pedagogy, egalitarianism, sociology, Teacher Professional Education (PPG)